2013
DOI: 10.1371/journal.pone.0054724
|View full text |Cite
|
Sign up to set email alerts
|

Skin Collagen Fiber Molecular Order: A Pattern of Distributional Fiber Orientation as Assessed by Optical Anisotropy and Image Analysis

Abstract: BackgroundBirefringence can reveal much of the morphology, molecular order, heterogeneity of fiber orientation, and nonlinear optical properties of biopolymers such as collagen. However, the detailed characterization of skin collagen fibers using optical anisotropy methods remains elusive. A clear understanding of collagen fiber organization in skin tissues may be important in the interpretation of their structural-functional relationships under normal and pathological conditions. In this study, fiber orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…The energy provided by LED therapy alters this condition, generating an environment that favors the formation of new blood vessels and proliferation of fibroblasts, which produce collagen fibers and extracellular matrix 8,15 . Several studies have demonstrated the action of LED during the early stages of tissue repair in a variety of clinical situations by the early activation of the inflammatory phase, significantly increasing fibroblast proliferation and reducing the inflammatory infiltrate 7,10 .…”
Section: Resultsmentioning
confidence: 99%
“…The energy provided by LED therapy alters this condition, generating an environment that favors the formation of new blood vessels and proliferation of fibroblasts, which produce collagen fibers and extracellular matrix 8,15 . Several studies have demonstrated the action of LED during the early stages of tissue repair in a variety of clinical situations by the early activation of the inflammatory phase, significantly increasing fibroblast proliferation and reducing the inflammatory infiltrate 7,10 .…”
Section: Resultsmentioning
confidence: 99%
“…18,19,41 At 14 days, the qualitative histological analysis showed a predominance of thick fibers (type I) in the group LED + D, when compared with the other groups, which is characteristic of the process of fibrillogenesis. 4,40,42 Moreover, in this experimental period, the animals in the groups treated with phototherapy (LED and LED + D) had statistically significant morphometric results regarding the deposition of collagenous fibers, when compared with the control. Considering the data obtained at this experimental time for the LED group, this result is probably due to the action of phototherapy, making energy available to the cells that were damaged by the surgical process, thus accelerating the repair process during its secondary phase.…”
Section: Discussionmentioning
confidence: 69%
“…1,2 It is critical for the formation of the extracellular matrix of connective tissue. 3,4 It is important to quantify this protein in skin wounds because its formation is associated with the tissue repair process. [3][4][5] The macroscopic and histomorphometric analyses provide qualitative and quantitative benefits in assessing the evolution of tissue repair process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations